Performance of Water Pump on Distribution and Transmission Process using Variable Speed Drive - Dwi Oktavianto Wahyu Nugroho; Totok Soehartanto; Tahta Anugrah Wibowo (Institut Teknologi Sepuluh Nopember, 2020)
The Pump is the vital component in the transmission of water from one unit to another or the distribution water from booster unit to customer. Water pumping has become ineffective due to incorrect installation of the installed pump not in accordance with the pre-installed piping. Investing in network development in the coming year is sometimes one of the reasons why pumps are installed improperly. Thus, high pressure pumps are sometimes installed at lower pipeline pressure. This condition usually does not only double between the pressure in the pipe and pump. Classically, pump output lines are usually coupled with valves (usually butterfly or rotary valves) to provide conditions that correspond to the pump's datasheet. Meanwhile, the classical concept will decrease the lifetime of pump, so the Variable Speed Drive (VSD) becomes the solution. TawangSari, SiwalanPanji, and KedungUling units are picture how VSD can fix kind of problem that faced in classical system. Worst energy use and decreased performance in classical system cause by wrong installation and limitation of supply power are solved by adapting frequency produced by VSD as it needed.